The cellular basis of increased PET hypoxia tracer uptake in focal cerebral ischemia with comparison between [18F]FMISO and [64Cu]CuATSM. Issue 3 (March 2021) - Little, Philip V; Arnberg, Fabian; Jussing, Emma; Lu, Li; Ingemann Jensen, Andreas; Mitsios, Nicholas; Mulder, Jan; Tran, Thuy A; Holmin, Staffan
PET hypoxia imaging can assess tissue viability in acute ischemic stroke (AIS). [ 18 F]FMISO is an established tracer but requires substantial accumulation time, limiting its use in hyperacute AIS. [ 64 Cu]CuATSM requires less accumulation time and has shown promise as a hypoxia tracer. We compared these tracers in a M2-occlusion model (M2CAO) with preserved collateral blood flow. Rats underwent M2CAO and [ 18 F]FMISO ( n = 12) or [ 64 Cu]CuATSM ( n = 6) examinations. [ 64 Cu]CuATSM animals were also examined with MRI. Pimonidazole was used as a surrogate for [ 18 F]FMISO in an immunofluorescence analysis employed to profile levels of hypoxia in neurons (NeuN) and astrocytes (GFAP). There was increased [ 18 F]FMISO uptake in the M2CAO cortex. No increase in [ 64 Cu]CuATSM activity was found. The pimonidazole intensity of neurons and astrocytes was increased in hypoxic regions. The pimonidazole intensity ratio was higher in neurons than in astrocytes. In the majority of animals, immunofluorescence revealed a loss of astrocytes within the core of regions with increased pimonidazole uptake. We conclude that [ 18 F]FMISO is superior to [ 64 Cu]CuATSM in detecting hypoxia in AIS, consistent with an earlier study. [ 18 F]FMISO may provide efficient diagnostic imaging beyond the hyperacute phase. Results do not provide encouragement for the use of [ 64 Cu]CuATSM in experimental AIS.